The Importance of Character Education in the World of Education - Disa Ariella Partiwi; Dewi Ratu Bilqis (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Character of education, it is absolutely necessary not only in school but also at home, in the social environment. Event now this is no longer a participant character of education early childhood through adolescence but also adults. Absolutely necessary for the survival of this nation. Competition imagine what will emerge in the next years. Obviusly it would be our burden and parent for today. At that time, the children will face competition with colleagues from various countries around the world. In fact we are still going to work year will feel the same feelings. Demand the quality of human resources in the coming millennium certainly requires good character. However, the character is the key individual goal.